Talent: the secret to being world class - Roebuck, Chris (Henry Stewart Talks, 2010)
Why good talent management and development is vital, What benefits does it bring?, What are most organizations doing?, How can you make it effective?, What are the roles of CEO and line management?, How can they be engaged in the implementation?, What do human resources do?, Strategic issues
Archived at 2025/05/28